Seroepidemiology of diphtheria and pertussis in Chongqing, China: serology-based evidence of Bordetella pertussis infection - Yao, N.; Zeng, Q.; Wang, Q. (Public health (London), 2018)
In order to gain further insight into the seroepidemiology of Bordetella pertussis infection and immunity against diphtheria in Chongqing, China, the concentrations of antibodies to pertussis toxin (PT) and diphtheria toxin (DT) were investigated in a healthy population. Cross-sectional study. In total, 1080 healthy people were recruited into this study. Sera antibodies to DT and PT were measured quantitatively using commercial enzyme-linked immunosorbent assay kits. Age-specific incidence of infection with B. pertussis was estimated and compared with notified cases of pertussis. The mean concentration of anti-DT IgG was 0.71 IU/ml (95% confidence interval [CI] = 0.60–0.82), with a positive rate (>0.01 IU/ml) of 97.41% (1052/1080). The mean concentration of anti-PT IgG was 7.65 IU/ml (95% CI = 6.65–8.65), with a positive rate (>100 IU/ml) of 1.17% (11/944). The estimated pertussis infection rate was 7290/100,000, which was far higher than the reported incidence of 1.29/100,000 in 2015. The peaks of estimated incidence of infection were found in subjects aged 7–14 years (9971/100,000) and ≥20 years (13,898/100,000). B. pertussis infection occurs frequently in young infants and adolescents/adults; the latter are often responsible for the transmission of pertussis to young infants. The existing surveillance system may underestimate the true incidence of pertussis in older age groups in Chongqing, and the immunisation programme should be improved to provide protection against pertussis for adolescents and young adults. •Seroepidemiology of pertussis in Chongqing indicated that the reported incidence was far more underestimated.•Bordetella pertussis infection occur frequently both in young infants and adults.•The existing surveillance system was inadequate of notifying minor pertussis of adults.•Vaccinating adults/adolescents in close contact with infants would be efficient to prevent the transmission.